Donor site healing in follicular unit extraction hair transplantation: current evidence, cellular mechanisms, and future research directions: Cellular responses in FUE donor area healing - Arencibia Pérez, Ney; Guerrero Roldán, María José (Cellular and Molecular Biology, 2025)
Follicular unit extraction (FUE) has become a leading technique in hair transplantation, yet optimal management of the donor area remains a clinical challenge. This systematic review analyzes intraoperative and postoperative interventions applied to the donor area in FUE hair transplantation, with a focus on both clinical outcomes and the cellular and molecular mechanisms involved in tissue repair, inflammatory response, and regenerative processes. A comprehensive literature search was conducted in PubMed and EMBASE (January 2000–June 2025), identifying clinical studies that evaluated donor area treatments and reported outcomes related to healing, inflammation, infection, and patient satisfaction. Four studies met the inclusion criteria, encompassing corticosteroid infiltration, platelet-rich plasma (PRP), timing of postoperative care, and hair follicle-derived microtissue (HFMT) application. Evidence suggests that intraoperative corticosteroid use significantly reduces postoperative edema, likely by modulating local inflammatory pathways and vascular permeability. Early postoperative wound care is associated with decreased folliculitis incidence, highlighting the importance of timely intervention in preventing microbial colonization and dysregulated immune responses. While PRP and HFMT show potential for enhancing cellular proliferation and accelerating wound closure, current data are limited by heterogeneity in study design and lack of standardized molecular endpoints. The review identifies a critical gap in mechanistic studies exploring the cellular dynamics of donor area healing, including the roles of keratinocytes, fibroblasts, and immune cells. Future research integrating molecular biomarkers and advanced imaging is needed to elucidate the pathways driving optimal tissue regeneration. These insights may inform evidence-based protocols that not only improve clinical outcomes but also advance our understanding of scalp wound biology in the context of FUE.